Identification of CD133-Positive Radioresistant Cells in Atypical Teratoid/ Rhabdoid Tumor - Chiou, Shih-Hwa (Public Library of Science, 2008)
Atypical teratoid/rhabdoid tumor (AT/RT) is an extremely malignant neoplasm in the central nervous system (CNS) which occurs in infancy and childhood. Recent studies suggested that CD133 could be considered a marker for brain cancer stem-like cells (CSCs). However, the role of CD133 in AT/RT has never been investigated. Herein we report the isolation of CD133-positive cells (CD133(+)), found to have the potential to differentiate into three germ layer tissues, from tissues of nine AT/RT patients. The migration/invasion/malignancy and radioresistant capabilities of CD133(+) were significantly augmented when compared to CD133(−). The clinical data showed that the amount of CD133(+) in AT/RTs correlated positively with the degree of resistance to radiation therapy. Using cDNA microarray analysis, the genotoxic–response profiles of CD133(+) and CD133(−) irradiated with 10 Gy ionizing radiation (IR) were analyzed 0.5, 2, 6, 12 and 24 h post-IR. We then validated these microarray data and showed increased phosphorylation after IR of p-ATM, p-RAD17, and p-CHX2 as well as increased expression of BCL-2 protein in CD133(+) compared to CD133(−). Furthermore, we found that CD133(+) can effectively resist IR with cisplatin- and/or TRAIL-induced apoptosis. Immunohistochemical analysis confirmed the up-regulated expression of p-ATM and BCL-2 proteins in IR-treated CD133(+) xenotransgrafts in SCID mice but not in IR-treated CD133(−). Importantly, the effect of IR in CD133(+) transplanted mice can be significantly improved by a combination of BCL-2 siRNA with debromohymenialdisine, an inhibitor of checkpoint kinases. In sum, this is the first report indicating that CD133(+) AT/RT cells demonstrate the characteristics of CSCs. The IR-resistant and anti-apoptotic properties in CD133(+) may reflect the clinical refractory malignancy of AT/RTs and thus the activated p-ATM pathway and BCL-2 expression in CD133(+) could be possible targets to improve future treatment of deadly diseases like AT/RT.